We are given transformation rule
(x, y) --> (x + 4, y + 7).
The coordinate of the pre-image is (4,5).
The coordinate of the transformed image is (0,-2).
Please see, if we apply
(x, y) --> (x + 4, y + 7) rule.
(4,5) coordinate would become (4 +4 , 5+7 ) = (8,12).
But we need (0,-2) instead of (8,12).
Let us reverse operation in the given rule and check.
Let us change (x + 4, y + 7) to (x-4, y-7) and now check.
(4,5) coordinate would become (4-4 , 5-7) = (0,-2).
So, we got exact coordinate of the transformed image.
Therefore, error was
(x, y) --> (x + 4, y + 7) rule should be (x, y) --> (x - 4, y - 7) rule.